2017
DOI: 10.1371/journal.pntd.0005560
|View full text |Cite
|
Sign up to set email alerts
|

Interruption of persistent exposure to leprosy combined or not with recent BCG vaccination enhances the response to Mycobacterium leprae specific antigens

Abstract: Household contacts of multibacillary leprosy patients (HCMB) constitute the group of individuals at the highest risk of developing leprosy. Early diagnosis and treatment of their index cases combined with Bacille Calmette-Guerin (BCG) immunization remain important strategies adopted in Brazil to prevent HCMB from evolving into active disease. In the present study, we assessed the impact of these measures on the immune response to Mycobacterium leprae in HCMB. Peripheral blood mononuclear cells (PBMC) from HCMB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 28 publications
0
12
0
3
Order By: Relevance
“…Besides reducing clinical leprosy among vaccinees, mainly of the MB type, recent data suggested that BCG vaccination of household contacts of MB leprosy patients may induce activation of T cell clones that recognize M . leprae specific antigens not shared with BCG [ 39 ]. The majority (92.5%) of schoolchildren diagnosed with leprosy in this study had one positive BCG scar and the PB form of the disease (80.0%).…”
Section: Discussionmentioning
confidence: 99%
“…Besides reducing clinical leprosy among vaccinees, mainly of the MB type, recent data suggested that BCG vaccination of household contacts of MB leprosy patients may induce activation of T cell clones that recognize M . leprae specific antigens not shared with BCG [ 39 ]. The majority (92.5%) of schoolchildren diagnosed with leprosy in this study had one positive BCG scar and the PB form of the disease (80.0%).…”
Section: Discussionmentioning
confidence: 99%
“…Although not recommended by the World Health Organization (WHO), the application of this vaccination specifically for leprosy prophylaxis is recognized by the WHO for its significant contribution to the decline in the incidence of the disease [ 7 , 24 ]. The BCG vaccine induces the activation of T-cell clones that recognize specific M. leprae epitopes, providing a protective effect against disease progression, including leading to negative PGL-I serological tests that were previously positive [ 6 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Contacts without a BCG scar or with just one are vaccinated, and with two scars they are not vaccinated. Currently there are still doubts as to whether BCG protects from leprosy [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although not recommended by the World Health Organization (WHO), the application of this vaccination speci cally for leprosy prophylaxis is recognized by the WHO for its signi cant contribution to the decline in the incidence of the disease (5,18). The BCG vaccine induces the activation of T-cell clones that recognize speci c M. leprae epitopes, providing a protective effect against disease progression, including leading to negative PGL-I serological tests that were previously positive (4,19).…”
Section: Discussionmentioning
confidence: 99%
“…Contacts without a BCG scar or with just one are vaccinated, and with two scars they are not vaccinated. And it is currently established that BCG provides some protection against leprosy (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%